O caso de Cariclo: refletindo sobre o papel dos astrônomos na Educação em Astronomia - Langhi, Rodolfo (Sociedade Brasileira de Física, 2017)
The interaction with amateur astronomers and professionals is a worldwide trend, with many discoveries and contributions from amateurs to the scientific community. A successful example of this collaboration was the discovery of the first ring system around a smaller body of the Solar System, the Centaur named Chariklo, which orbits the Sun in a region between Saturn and Uranus. Some amateur astronomers from Brazil participated in the international work team whose observations were essential for this discovery. However, Cariclo's case leads us to reflect more closely on the expansion of this relationship of amateurs and professionals to another sphere: the School. In this sense, the union of astronomers (professionals and amateurs) and the education has resulted in benefits to the education of some countries and the teachers formation about contents and methodologies of Astronomy teaching. In Brazil, one of these examples is the International Year of Astronomy, which left as a legacy important reflections about the role of astronomers in Astronomy Education, which we also discussed in this article, ending with a list of challenges and possibilities for our country.

A interação entre astrônomos amadores e profissionais em Astronomia é uma tendência mundial, sendo muitas as descobertas e contribuições dos amadores à comunidade científica. Um exemplo bem-sucedido desta colaboração foi a descoberta do primeiro sistema de anéis ao redor de um corpo menor do Sistema Solar, o centauro denominado Cariclo, que orbita o Sol numa região entre Saturno e Urano. Participaram da equipe internacional de trabalho alguns astrônomos amadores do Brasil cujas observações foram essenciais para esta descoberta. Porém, o caso de Cariclo leva-nos a refletir com mais propriedade sobre a ampliação desta relação entre amadores e profissionais para outra esfera: a escolar. Neste sentido, a atuação conjunta de astrônomos (profissionais e amadores) na educação tem resultado em benefícios à educação de alguns países e à formação de professores com relação a conteúdos e metodologias de ensino de Astronomia. No Brasil, um dos exemplos de destaque é o Ano Internacional da Astronomia, que deixou como legado importantes reflexões sobre o papel dos astrônomos na Educação em Astronomia, o qual também discutimos neste artigo, finalizando com um elenco de desafios e possibilidades para nosso país.
The case Chariklo: reflecting about the role of astronomers in Astronomy Education
Keywords: Astronomy Education; professional astronomer; amateur astronomer; minor planets of Solar System; Educação em Astronomia; astronomia profissional; astronomia amadora; corpos menores do Sistema Solar